Kebiasaan Makanan Ikan Baronang Lingkis (Siganus canaliculatus Park, 1797) di Perairan Selat Makassar (Food habits of White-Spotted Spinefoot (Siganus canaliculatus Park, 1797) in Makassar Strait) - Suwarni, Suwarni (Program Studi Manajemen Sumber Daya Perairan, 2018)
White-Spotted Spinefoot (Siganus canaliculatus Park, 1797) is one of fishery commundities that has many potentials to be developed. This research aims to know the food habits of White-Spotted Spinefoot caught in the waters of Makassar Strait. The sample collection conducted from March 2014 through April 2016 in the earn from the landing place of the fish of Paotere in Makassar. The analysis of the samples carried out in the Laboratory of Fish Biology, Department of Fisheries, Hasanuddin University, Makassar. The number of samples obtained during the research of 145 the number of fish consists of 128 fish males and 17 females fish. Based on the results of the analysis of the White-Spotted Spinefoot fish eating habits lingkis time-based sampling, gender, body size and the type of food eaten by fish Lingkis most White-Spotted Spinefoot i.e. Bacillariophyceae. Time-based sampling, Bacillariophyceae. Most in the packed in April, with the value of 84,9552%. Based on the gender of Bacillariophyceae worth respectively 76,0911%% in fish 78.6527 fish% males and females. A comparative analysis of the results of long gastrointestinal (gut) tool with a body length of fish then fish White-Spotted Spinefoot Lingkis are herbivores.Keywords: White-Spotted Spinefoot, food habits, Makassar Strait